1991
DOI: 10.1103/physreva.44.2578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aggregations in water–2-butoxyethanol mixtures by ultrasonic and Brillouin light-scattering measurements

Abstract: By means of ultrasonic and Brillouin light-scattering techniques, we have performed extensive measurements of the attenuation coefficient and sound velocity in 2-butoxyethanol aqueous solutions over a large temperature range. In the more concentrated solutions, the frequency dependence of these properties is well accounted for by a double relaxation time equation thus excluding contributions from concentration fluctuations. This finding, as well as the overall behavior as a function of concentration and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…As noted in the Introduction, there have been a number of studies using light scattering and SANS ,, experiments aimed at probing the existence and size of aggregates in BE–water solutions. The experimental size estimates are also based on the assumption of spherical aggregates, and in general, for comparable concentrations and temperatures, the radii reported are in qualitative accord with our estimates based on r cross .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in the Introduction, there have been a number of studies using light scattering and SANS ,, experiments aimed at probing the existence and size of aggregates in BE–water solutions. The experimental size estimates are also based on the assumption of spherical aggregates, and in general, for comparable concentrations and temperatures, the radii reported are in qualitative accord with our estimates based on r cross .…”
Section: Resultsmentioning
confidence: 99%
“…We report a molecular dynamics simulation investigation of aqueous 2-butoxyethanol (BE, CH 3 –(CH 2 ) 3 –O–(CH 2 ) 2 –OH) solutions. BE–water solutions have been studied extensively by a variety of experimental methods, and many physical properties have been shown to undergo rather dramatic changes on variation of composition and temperature. , ,, In particular, for BE–water solutions, densities, refractive indices, surface tensions, excess molar volumes, , ultrasonic speeds, , vapor pressures, heat capacities, ,, and excess thermodynamic properties ,,, have been reported. We note that, in addition to the usual partial molar properties, Koga and co-workers ,,,, have obtained so-called “third and fourth derivative” quantities, which provide strong signals of unusual behavior in BE–water and other aqueous systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of these experiments are reported elsewhere [7,8,12]. We found that the x, T, and co dependence of c and a in the three investigated solutions are qualitatively similar, but rather anomalous.…”
Section: Sound Propagation Measurementsmentioning
confidence: 53%
“…In particular, the phase diagram presents a lower critical solution temperature. Direct confirmation of the presence of micellar aggregates in this mixture has been obtained by light scattering [10][11][12] and, recently, by small-angle neutron scattering [ 13,14].…”
Section: Introductionmentioning
confidence: 95%